A Critical Analysis of the Application of State Aid Rules to Sport. Issue 2 (April 2015) - Nicolaides, Phedon
This article examines the application of state aid rules to sport and sport infrastructure. Sporting activities and their public financing fall within the scope of Article 107(1) TFEU when such activities are economic in nature. The article examines under which conditions sport is an economic activity. The public funding of sport infrastructure such as stadiums and arenas raises state aid issues at four levels: The owners of the infrastructure, the constructors, the operators, and the users. This article examines the conditions under which state aid is either removed or made to be compatible with the internal market.